Global influence of inventions and technology sovereignty - Philipp Boeing; Elisabeth Mueller (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
The global economic landscape has fundamentally shifted from the paradigm of globalization to renewed concerns regarding the risks and rewards of technological interdependence. This shift has sparked a critical discussion on technology sovereignty. This concept refers to a country's ability to provide essential technologies for competitiveness and welfare, and to develop or acquire them from other geographic areas without being unilaterally dependent on any particular one. We analyze the technology sovereignty of the world's leading innovators, including Europe, the US, China, Japan and Korea. By examining citation data from the universe of PCT patent applications, we determine the strength and direction of inventions' influence at global and bilateral levels to assess each geographic area's technology sovereignty. Our analysis shows that the US holds substantial technology sovereignty due to its leading global and bilateral influence. Despite ongoing US-European integration, their global positions differ, as Europe is dependent on all other areas except China. Although China has globally filed the most patent applications in recent years, bilaterally it remains dependent on all other geographic areas. Moreover, only Japan and Korea show a recent decline in their global influence.
Keywords: 330